Pulmonary metastasis of giant cell tumor of bone 29 years after local recurrence resection: implications for Long-Term surveillance - Qiushi Bai; Xiao Chang; Xiongfei Zou; Baozhong Zhang (Discover Oncology)
Abstract Background Pulmonary metastases of giant cell tumor of bone (GCTB) are rare and typically occur within several years of initial diagnosis or local recurrence. Here, we report a case with the longest documented interval—29 years—between the last local recurrence of GCTB and pulmonary metastasis, highlighting the need for long-term surveillance. Case presentation A 52-year-old female presented with an incidental pulmonary nodule detected 29 years after wide resection of recurrent GCTB in the left humeral head. Initial suspicion of primary lung cancer led to thoracoscopic lobectomy, which identified the nodule as a giant cell tumor through histopathological examination. Immunohistochemistry confirmed the diagnosis. This case emphasizes the potential for extremely delayed metastases of GCTB, likely due to the slow-growing nature of metastatic lesions. The findings underscore the challenges of distinguishing metastatic GCTB from primary lung cancers, which may result in overtreatment. Conclusion This report underscores the necessity of long-term surveillance for high-risk GCTB patients, even decades after treatment. It also highlights the unique biology of GCTB metastases, warranting further research into mechanisms and tailored management strategies.